Pathological and metabolic effects of a simulated Karenia mikimotoi bloom on hybrid abalone (Haliotis discus hannai♀ × H. fulgens♂) - Liao, Hailin; Xu, Xin; Zhuang, Yuye; Zhang, Yue; Li, Jing; Zhang, Qian; Ding, Zhenning; Wu, Yijing; Zhang, Peipei; Yang, Jie (Frontiers in Marine Science, 2025)
The hybrid abalone (Haliotis discus hannai ♀ × H. fulgens ♂), locally known as Lvpan abalone, is a commercially important aquaculture species in Fujian Province, China and is valued for its heat tolerance, rapid growth, and large size. While blooms of the dinoflagellate Karenia mikimotoi cause substantial losses in Fujian’s abalone industry primarily through toxin production and hypoxia, their specific effects on Lvpan abalone remain poorly characterized. This study investigated the 24-h and 48-h exposure effects of a simulated K. mikimotoi bloom on the gills and hepatopancreas of Lvpan abalone. Histopathology revealed significant tissue damage, along with oxidative stress that was confirmed by elevated levels of superoxide dismutase, catalase, and malondialdehyde. Metabolomic profiling uncovered a tissue-specific response. Both tissues exhibited shared responses to mitigate oxidative stress and regulate energy balance, mediated by the accumulation of β-hydroxybutyric acid and acetyl-L-carnitine. In addition, the gills maintained energy homeostasis through AMPK activation, whereas the hepatopancreas enhanced its detoxification capacity through elevated levels of S-adenosylmethionine. These findings elucidate the impact of K. mikimotoi blooms on Lvpan abalone and provide a scientific basis for developing mitigation strategies against toxic algal blooms in abalone aquaculture.